Extra nodal Rosai Dorfman disease of nasal septal mucosa without lymphadenopathy (Journal of Pathology of Nepal, 2016)
Rosai–Dorman disease, also known as sinus histiocytosis with massive lymphadenopathy, typically presents as massive enlargement of lymph nodes accompanied by systemic symptoms. Extranodal involvement is also known usually in head and neck regions. Rarely the disease presents at extranodal sites only without involvement of lymph nodes.We present a case of 58 years-old female who presented with mass in nasal septum without involvement of lymph nodes. The mass was removed surgically and diagnosis was made on histological grounds with classical indings of histiocytic proliferation and emperipolesis.